Crack Simulation on Diesel Engine Crankshaft using Finite Element Method - Pradhana Kurniawan; Yusuf Prasetyo Gemilang (TRANSMISI, 2023)
Crankshaft is a machine component that has a high stress value and failure usually occurs due to fatigue. Crankshaft in diesel engines found in certain vehicles that have performance specifications of 140 cv (cheveaux vapeur) at engine speed of 4000 rpm and displacement of 1963m3. Crankshaft failed on the crankpin and main bearing cap. The failure occurred after this vehicle traveled 180,000 km in use and through repairs during 8 years of use. Failure of the crankshaft is the root cause of internal damage to the combustion engine. Based on a simulation on a 4-cylinder diesel engine crankshaft using the finite element method using ANSYS Workbench 18.1 software, the equivalent (von mises) stress results are obtained with a maximum stress value of 445.72 MPa. Stress concentrations present in the crankshaft will result in the initiation of cracks which can propagate and result in fracture of the crankshaft. The stress concentration lies in the fillet web of the crankshaft where this part is very susceptible to cracking and fracture if the fillet design is not suitable or if an error occurs when the crankshaft is in the initial machining process. Stress concentrations at a certain point can also be caused by errors during the fabrication process.